(3MjGI GdMjhGfs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3SjO eMQe Hf SjO Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa fhY GdEfSGf , HGdGUZQjf GdbdH hGddSGf (B,(3HYO agPG cJGH de jSCdfi CMO JUfjag EfeG OYGfi Cfg hbY ai HYV GdOQhS PcQ eGdc GdMRjf aGSJNQJ Gddg ai hVY cJGH ai gPG GdTCf , hSejJg MjGI GdMjhGf s
(3BNQgG (B:s
(3hgPG eG GfJgi Edjg GdZQV eeG jMUd ai gPG GdTCf (B,(3MSHfG Gddg hcai s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3YdjgG JedcGJ BNQgG SfI (B1121(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs